2020
DOI: 10.1021/acssuschemeng.9b07360
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Coal Fly Ash as a Stabilizer for the Development of Ni/CaO-Based Bifunctional Material

Abstract: Sorption-enhanced glycerol steam reforming (SEGSR) is considered as one of the promising processes for H2 production by combining glycerol steam reforming with simultaneous CO2 capture in a single-unit operation. The key challenge for a successful SEGSR process is the selection of suitable high-temperature CO2 sorbents with high resistance to sintering. In the present work, an attempt was made to modify a CaO-based sorbent by adding different types of coal fly ash (FA1–FA12) to develop highly effective and eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recently, a shift of interest towards industrial waste solid residues as reforming catalysts can be observed, such as coal bottom ash catalysts, 71 metallurgical waste-driven catalysts, 72 and fly ash catalysts. 73 The main reasons for exploiting industrial waste solid residues as catalysts are their low-cost characteristic and the high contents of alkali, alkaline earth, and transition metal oxides ( e.g. , Al 2 O 3 , SiO 2 , MgO, and CaO).…”
Section: Global Market Of Biochemical Production From Glycerolmentioning
confidence: 99%
“…Recently, a shift of interest towards industrial waste solid residues as reforming catalysts can be observed, such as coal bottom ash catalysts, 71 metallurgical waste-driven catalysts, 72 and fly ash catalysts. 73 The main reasons for exploiting industrial waste solid residues as catalysts are their low-cost characteristic and the high contents of alkali, alkaline earth, and transition metal oxides ( e.g. , Al 2 O 3 , SiO 2 , MgO, and CaO).…”
Section: Global Market Of Biochemical Production From Glycerolmentioning
confidence: 99%
“…The successful development of the SESR process relies on the type of the employed catalyst and sorbent, as well as their mixing pattern, i.e., physical mixing or integrating the catalyst and sorbent into a single particle. , Regarding the type of catalyst and sorbent, Ni-based catalysts and CaO-based sorbents have received the most attention due to their high ability to, respectively, break C–C bonds and capture CO 2 , high availability, and low cost. , Concerning the mixing pattern, the CO 2 produced during the SR and WGS reactions needs to diffuse from the interior surface of the catalyst through the catalyst pore structure and the bulk of the fluid to the neighboring sorbent where it can be adsorbed in the case of physical mixing. Nevertheless, the direct on-site sorption of CO 2 can be realized if the catalyst and sorbent are integrated into a single particle, i.e., bifunctional catalyst sorbent. , Therefore, since the late 2000s, Ni–CaO-based catalyst-sorbent bifunctional materials have been receiving more and more attention for high-purity hydrogen production via SESRG process. However, carbon deposition on Ni active sites can not only decrease the catalytic activity of the Ni–CaO-based bifunctional materials but also reduce the access of CO 2 to active CaO sites by blocking the pores and/or adhering to the surface of the sorbent at high temperatures . Embedding Ni in the NiAl 2 O 4 spinel structure, which provides a high distribution of small Ni active sites after reduction, has been well recognized as one of the most efficient approaches to reduce coke formation on metallic Ni. , However, the thermodynamic stability of NiAl 2 O 4 inhibits the diffusion of Ca 2+ into this spinel structure to create a close contact with Ni and Al species.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, Gao and coworkers utilized coal fly ash as the support for bifunctional Ni-CaO materials for SESRG, achieving H 2 production with 97% purity and 90% yield for 20 cycles. 15 Dang et al also reported 96% H 2 was produced over MgO-promoted Ni-CaO bifunctional materials via SESRG. 16 These results unambiguously suggest that SESRG is practically feasible for producing high-purity H 2 and reducing carbon emission.…”
mentioning
confidence: 97%